Strategi Membangkitkan Kembali Wisata Setigi Di Kabupaten Gresik Pasca Pandemi COVID-19 - Noviyanti, Upik Dyah Eka; Elia, Angeli Herdarianti Sabath (JURNAL DESTINASI PARIWISATA; Vol 10 No 2 (2022): VOL 10, NO 2 (2022): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2022)
Due to the spread of the COVID-19 virus in Indonesia, the number of tourist arrivals to Indonesia fell in 2020. The COVID-19 virus has paralyzed the tourism industry. Setigi is one of the tourist attractions that have been affected by the pandemic. Before the pandemic, Setigi was one of the popular tourist destinations in Gresik, East Java. During the pandemic, tourists began to stop coming, which caused a decline in the number of visitors at Setigi.The research was carried out using the qualitative method, which resulted in descriptive data, to facilitate obtaining information. Data collection techniques used were interview, observation, and documentation techniques. This study aims to discover what strategies are carried out by Setigi managers to increase the number of visitors during the pandemic and what obstacles the managers face during the strategy implementation process. The author’s research results are the strategies the manager carried out to raise the number of tourists during the pandemic; the first is to promote Setigi Tourism’s official account on social media platforms like Instagram, Facebook, and Twitter. During the pandemic, promotional activities using social media have been an effective way to do. The second strategy is to strengthen health protocols in tourist attractions by installing hygiene instruments and continuously monitoring the tourist attraction area’s condition. The third strategy is the improvement of facilities and services in tourist attractions, employees are required to welcome tourists in a friendly and polite manner and not forget to remind tourists about health protocols. Keyword: Tourism, COVID-19, pandemic, health protocol, promotion, Setigi.